Editorial Norms - Gaceta, Laboral (Gaceta Laboral, 2020)
I. Instructions for authors of articles1) Gaceta Laboral: is an arbitrated scientific publication published quarterly, which specializes in social work and social policy. The purpose of the publication is to stimulate and publish scientific publications written in any language, but preferibly in Spanish or English, from any analytical perspective, and promotes no particular orientation or school of thought.The publication only considers un-edited papers, which have not been simultaneously offered to other journals, for publication.Gaceta Laboral does not accept responsibility for opinions emitted by the authors.